Harnessing cytokines: innovative adjuvants for improved veterinary vaccine efficacy - Yan, Shihong; Chen, Huimin; Liu, Qiao; Zhang, Xinyu; Wei, Qiulu; Hu, Chenqi; Chu, Dianfeng; Diao, Hongxiu; Liu, Shasha; Chen, Ji-Long (Frontiers in Immunology, 2025)
Vaccination is one of the most effective methods for controlling animal infectious diseases, and the use of adjuvants plays crucial role in enhancing the immune efficacy of vaccines, particularly in inactivated and subunit vaccines. With the continuous advancement of research in animal immunology and immune mechanisms, our understanding of the functions of cells and cytokines in immune responses has become increasingly comprehensive, laying a solid foundation for the development of novel vaccines and adjuvants. Cytokines are a class of proteins secreted by the animal body that regulate innate and adaptive immune responses through interaction with specific receptors. To date, numerous studies have investigated the potential of using cytokines as adjuvants to enhance the efficacy of veterinary vaccines. This review focuses on cytokines as veterinary vaccine adjuvants, with special attention to the current research progress and mechanisms of cytokines such as interleukins, interferons, chemokines, and colony-stimulating factors. Additionally, examples of the application of cytokine-based adjuvants in combination with veterinary vaccines will be discussed to provide further insights and references for the development of cytokine-based veterinary adjuvants.